THE BUSINESS PLAN OF PARENTING APPLICATION “PARENTS JOURNEY” - Luthfiana Supangkat; Bambang Purwoko Kusumo Bintoro (Sean Institute, 2023)
Parents Journey is a technology company focused on parenting application. Parents Journey provides all the information needed for parents or guardians of early childhood (0 - 6 years) in the form of a mobile application platform. This business plan preparation aims to analyze the market, technical and operational, risks, legal and legality, and financial aspects. This business plan preparation is supported by research through online survey methods which are analyzed using descriptive statistical methods and interviews with purposive sampling technique. Using a marketing strategy with the Segmentation, Targeting, Positioning (STP) method, 7P Marketing Mix, Digital Marketing Funnel, and a business model with the Business Model Canvas (BMC), it is known that the Parents Journey has an advantage over competitors with eighteen features that can help parents/guardians in providing early childhood care. The business idea is feasible in the best-case scenario with a payback period of 1.42 years (below 5 years), positive NPV, has a greater IRR value (78% -79%) than the MARR (10%), and the PI value of 4,65.